The Effect of Zikir Relaxation in Counseling to Reduce Internet Addiction - Irman Irman; Che Zarrina Saari; Silvianetri Silvianetri; Khairunnas Rajab; Muhammad Zalnur (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
The high number of internet addiction experienced by students has been increasing for last decades. The addiction can potentially damage the brain's nerve cells, which in turn affect students' cognitive, emotion and behavior. Thus, an effective treatment is urgently needed. One of the alternatives is by employing the zikir relaxation in counseling. This study aims find the effect of zikir relaxation in counseling as the attempt to reduce the anxiety due to the internet addiction of high school students. The research method used experiment method specifically, the pretest and posttest control group design. There were 10 students taken through the random sampling. Data analysis used independent t test. The results of the study found that: (1) there was a difference level of anxiety reduction due to internet addiction for the students who received the treatment compared those who did not get, and (2) there was a significant influence between remembrance relaxations in counseling on student anxiety reduction in internet addiction. This implies that zikir relaxation is effective to use by counselors in schools to handle internet addiction